Determination of Competition Conventional Bank in Banking Industry in Indonesia - Ciplis Gema Qori’ah; Mochammad Ridwan G.; Adhitya Wardhono; Ika Nurjannah (Economics and Finance in Indonesia, 2016)
The aim of this study is to determine the level of concentration and competition behavior of conventional commercial banks in the national banking industry. This study focuses on descriptive analysis and quantitative analysis using panel data regression for 9 conventional commercial banks during 2003–2014. Results of eclectic analysis are supposed that behavior of banks is less competitive due to high levels of concentration in the banking industry. While the results of panel data regression show that the variables of bank interest expense, operating expense, other operating incomes and variable of loanable funds significantly affect the income of conventional banks.AbstrakTujuan dari penelitian ini adalah untuk mengetahui tingkat konsentrasi dan perilaku persaingan bank umum konvensional yang terdapat di industri perbankan nasional. Penelitian ini memfokuskan pada analisis deskriptif dan analisis kuantitatif dengan menggunakan regresi data panel dengan sampel 9 bank umum konvensional selama 2003–2014. Hasil analisis menunjukkan bahwa perilaku bank kurang kompetitif karena tingkat konsentrasi yang tinggi di industri perbankan. Sedangkan hasil menunjukkan regresi data panel bahwa variabel beban bunga bank, beban operasional, pendapatan operasional lainnya, dan dana pinjaman signifikan berpengaruh pada pendapatan bank konvensional. Kata kunci: Kompetisi Bank; Regresi Data Panel; Industri PerbankanJEL classifications: B21; C23; L80